Nature of Stressors on Female Law Enforcement Academy Recruits - Dillard, Sandra Patricia (2019)
A problem in law enforcement academy training is that female recruits endure more stressors than male recruits endure. This can lead to fewer females opting for careers as law enforcement officers. The purpose of this study was to explore the unique stressors on female recruits when they are held to the same standards as males. The feminist theory was used as the theoretical framework for this study to depict how stress is perceived for the female. The first research question examined how outside stressors affected female trainees. The second research question examined how job-related stressors affected female trainees. In-depth, semistructured interviews with students that were enrolled in a basic law enforcement academy at a Southeastern United States training center were conducted using a phenomenological qualitative approach. Thirty-two students were eligible for the study and 18 students participated. Data were analyzed using precoding of the transcription. Next, open coding, descriptive coding, and pattern coding were used to arrive at themes in the data. The results for the first research question showed that female trainees were affected regarding how they believe they are seen in society, how they are perceived in the family role, and how their peers view them as fellow future officers. The results for the second research question showed that female trainees are affected by being the sexual minority in their field, by negative male peer perception, by the treatment and acceptance by their superiors, by the potential career risks of this selection, and by the lack of time left for their personal well-being. This research is useful to law enforcement to discern that female trainees have a higher level of stress over males and measures can be adopted through hiring and retention to result in positive social change